First Food and Drug Administration Cleared Thin-Film Electrode for Intracranial Stimulation, Recording, and Monitoring of Brain Activity—Part 1: Biocompatibility Testing - Kullmann, Aura; Kridner, Debra; Mertens, Steve; Christianson, Mark; Rosa, Dave; Diaz-Botia, Camilo A. (Frontiers in Neuroscience, 2022)
Subdural strip and grid invasive electroencephalography electrodes are routinely used for surgical evaluation of patients with drug-resistant epilepsy (DRE). Although these electrodes have been in the United States market for decades (first FDA clearance 1985), their fabrication, materials, and properties have hardly changed. Existing commercially available electrodes are made of silicone, are thick (>0.5 mm), and do not optimally conform to brain convolutions. New thin-film polyimide electrodes (0.08 mm) have been manufactured to address these issues. While different thin-film electrodes are available for research use, to date, only one electrode is cleared by Food and Drug Administration (FDA) for use in clinical practice. This study describes the biocompatibility tests that led to this clearance. Biocompatibility was tested using standard methods according to International Organization for Standardization (ISO) 10993. Electrodes and appropriate control materials were bent, folded, and placed in the appropriate extraction vehicles, or implanted. The extracts were used for in vitro and in vivo tests, to assess the effects of any potential extractable and leachable materials that may be toxic to the body. In vitro studies included cytotoxicity tested in L929 cell line, genotoxicity tested using mouse lymphoma assay (MLA) and Ames assay, and hemolysis tested in rabbit whole blood samples. The results indicated that the electrodes were non-cytotoxic, non-mutagenic, non-clastogenic, and non-hemolytic. In vivo studies included sensitization tested in guinea pigs, irritation tested in rabbits, acute systemic toxicity testing in mice, pyrogenicity tested in rabbits, and a prolonged 28-day subdural implant in sheep. The results indicated that the electrodes induced no sensitization and irritation, no weight loss, and no temperature increase. Histological examination of the sheep brain tissue showed no or minimal immune cell accumulation, necrosis, neovascularization, fibrosis, and astrocyte infiltration, with no differences from the control material. In summary, biocompatibility studies indicated that these new thin-film electrodes are appropriate for human use. As a result, the electrodes were cleared by the FDA for use in clinical practice [510(k) K192764], making it the first thin-film subdural electrode to progress from research to clinic. Its readiness as a commercial product ensures availability to all patients undergoing surgical evaluation for DRE.